2003
DOI: 10.1093/nar/gkg284
|View full text |Cite
|
Sign up to set email alerts
|

Scp160p associates with specific mRNAs in yeast

Abstract: Scp160p is a multiple KH-domain RNA-binding protein in yeast that has been demonstrated previously to associate with both soluble and membrane-bound polyribosomes as an mRNP component. One key question that has remained unanswered, however, is whether the mRNAs in these mRNP complexes are random or specific. We have addressed this question using microarray analyses of RNAs released from affinity isolated Scp160p-containing complexes, compared with total RNA controls from the same lysates. Our results, confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 15 publications
5
45
0
Order By: Relevance
“…We fractionated polysomes from wild-type, Dscp160, Dbfr1 and Dbfr1 Dscp160 cells on a sucrose gradient and subjected the polysome fractions to immunoblot analysis. As previously observed (Baum et al, 2004;Li et al, 2003), we did not find a significant change in the polysome profile or an increase in the 80S monosome fraction in any of the strains, which would be indicative of translation attenuation (Fig. 4A).…”
Section: Screen For Novel P-body-interacting Proteins At the Endoplassupporting
confidence: 86%
“…We fractionated polysomes from wild-type, Dscp160, Dbfr1 and Dbfr1 Dscp160 cells on a sucrose gradient and subjected the polysome fractions to immunoblot analysis. As previously observed (Baum et al, 2004;Li et al, 2003), we did not find a significant change in the polysome profile or an increase in the 80S monosome fraction in any of the strains, which would be indicative of translation attenuation (Fig. 4A).…”
Section: Screen For Novel P-body-interacting Proteins At the Endoplassupporting
confidence: 86%
“…In response to SPB duplication defects, the SESA network, comprising of the known mRNA-binding protein Scp160 (Frey et al 2001;Li et al 2003Li et al , 2004Baum et al 2004), the ribosomeassociated Asc1 (Baum et al 2004;Gerbasi et al 2004), the translation inhibitor Eap1 (Cosentino et al 2000), and the protein Smy2 (Kofler et al 2005), was identified as being responsible for the translation control of POM34 mRNA. We demonstrate that SESA inhibits translation of POM34 mRNA by binding of the 4E-BP Eap1 to the conserved translation initiation factor eIF4E.…”
Section: Discussionmentioning
confidence: 99%
“…A microarray analyses of mRNAs released from affinity isolated Scp160-containing complexes identified a limited set of mRNAs that bind to Scp160 . We tested the two most prominent mRNAs identified by Li et al (2003), the DHH1 and YOR338w transcripts, but did not find an enrichment of these mRNAs in anti-Smy2 immunoprecipitates nor any importance of the genes for survival of mps2D 2mm-SMY2 cells (B Sezen, unpubl.). Furthermore, a recent study identified mainly mRNAs coding for proteins of the cell wall, plasma membrane, ER and nucleolus in association with Scp160 (Hogan et al 2008).…”
Section: Sesa Binds To Pom34 Mrnamentioning
confidence: 99%
“…In particular, it was reported that Scp160p binds to ribosomes (13)(14)(15) and associates to a small subset of specific mRNAs (8), suggesting a contribution to their stabilization, processing and/or translation. The TPE phenotype of ⌬scp160 cells may, therefore, reflect the contribution of Scp160p to the post-transcriptional regulation of specific mRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this molecular organization, several multi-KH domain proteins have been shown to bind single-stranded nucleic acids with high affinity, in vitro. Multi-KH domain proteins were proposed to participate in different aspects of RNA metabolism from the interaction with specific mRNAs (1,8) to tRNA export and the general regulation of mRNA translation and protein synthesis (9 -12). In particular, in S. cerevisiae, Scp160p is found associated to both soluble and membranebound polyribosomes (13)(14)(15).…”
mentioning
confidence: 99%